2018
DOI: 10.1080/15384101.2018.1502575
|View full text |Cite
|
Sign up to set email alerts
|

Expression of circular RNAs during C2C12 myoblast differentiation and prediction of coding potential based on the number of open reading frames and N6-methyladenosine motifs

Abstract: The importance of circular RNAs (circRNAs) as regulators of muscle development and muscle-associated disorders is becoming increasingly apparent. To explore potential regulators of muscle differentiation, we determined the expression profiles of circRNAs of skeletal muscle C2C12 myoblasts and myotubes using microarray analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to explore circRNA functions. We also established competing endogenous RNA (ceRNA) networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 53 publications
(92 reference statements)
2
26
0
Order By: Relevance
“…Myh1 was important for the fast-twitch muscle fibers, Myh7 contributed to the slow-twitch muscle fibers, while Myh2 acted as an intermediator between Myh1 and Myh7 [44,45]. Myh1, Myh2, and Myh7 were the signature genes of myoblast differentiation [46]. Our data displayed that the up-regulated expression of miR-133a inhibited the expression of two potential target genes (Myh1 and Myh7) with age.…”
Section: Discussionmentioning
confidence: 63%
“…Myh1 was important for the fast-twitch muscle fibers, Myh7 contributed to the slow-twitch muscle fibers, while Myh2 acted as an intermediator between Myh1 and Myh7 [44,45]. Myh1, Myh2, and Myh7 were the signature genes of myoblast differentiation [46]. Our data displayed that the up-regulated expression of miR-133a inhibited the expression of two potential target genes (Myh1 and Myh7) with age.…”
Section: Discussionmentioning
confidence: 63%
“…102 circFGFR4 binding to miR-107 promotes cell differentiation by targeting Wnt3a in bovine primary myoblasts. 95 Our research group has identified the coding potentials and known functional domains of 75 circRNAs during mouse C2C12 myoblast differentiation, 30 as well as 71 circRNAs with coding potential and known functional domains during pathological conditions of Co (II) ion-induced myocytotoxicity in mouse skeletal 108 In the future, other circRNAs encoding proteins involved in muscle development may be discovered. 104 Moreover, circSNX29 sponges miR-744 to facilitate bovine myoblasts differentiation and inhibit cell proliferation by activating the Wnt5a/Ca 2+ signalling pathway.…”
Section: Muscle Developmentmentioning
confidence: 99%
“…107 In addition to promoting proliferation, circ-ZNF609 is translated into a protein, but the function of the flagged protein is unknown in human myoblasts. 95 Our research group has identified the coding potentials and known functional domains of 75 circRNAs during mouse C2C12 myoblast differentiation, 30 as well as 71 circRNAs with coding potential and known functional domains during pathological conditions of Co (II) ion-induced myocytotoxicity in mouse skeletal 108 In the future, other circRNAs encoding proteins involved in muscle development may be discovered.…”
Section: Muscle Developmentmentioning
confidence: 99%
See 2 more Smart Citations